Investigating the Pea Virome in Germany—Old Friends and New Players in the Field(s) - Gaafar, Yahya Z. A.; Herz, Kerstin; Hartrick, Jonas; Fletcher, John; Blouin, Arnaud G.; MacDiarmid, Robin; Ziebell, Heiko (Frontiers in Microbiology, 2020)
Peas are an important legume for human and animal consumption and are also being used as green manure or intermediate crops to sustain and improve soil condition. Pea production faces constraints from fungal, bacterial and viral diseases. We investigated the virome of German pea crops over the course of three successive seasons in different regions of pea production to gain an overview of the existing viruses. Pools from 540 plants, randomly selected from symptomatic and asymptomatic pea, and non-crop plants surrounding the pea fields were used for ribosomal RNA-depleted total RNA extraction followed by high-throughput sequencing and RT-PCR confirmation. Thirty-five different viruses were detected in addition to nine associated nucleic acids. From these viruses, 25 are classified as either new viruses, novel strains or viruses that have not been reported previously from Germany. Pea enation mosaic virus 1 and 2 were the most prevalent viruses detected in the pea crops, followed by pea necrotic yellow dwarf virus and turnip yellows virus which was also found also in the surrounding non-legume weeds. Moreover, a new emaravirus was detected in symptomatic peas in one region for two successive seasons. Most of the identified viruses are known to be aphid transmissible. The results revealed a high virodiversity in the German pea fields that poses new challenges to diagnosticians, researchers, risk assessors and policy makers, as the impact of the new findings are currently unknown.